Analytic Theology as Sapiential Theology: Reflections on a Concern Raised by Kevin J. Vanhoozer - Wessling, Jordan (Open theology, 2017)
In a recent essay, the prolific and influential evangelical theologian, Kevin J. Vanhoozer, claims that analytic theology "is one of the major developments of our time, boasting annual conferences, a manifesto, and an online journal." Vanhoozer mentions the rise of analytic theology not to celebrate its success but to offer a cautionary note to those who are inclined to practice theology in an analytic key. One of the concerns that Vanhoozer raises is that the analytic method falls short of what we might call "sapiential theology"-roughly, theology that facilitates the acquisition of wisdom. In this paper, I examine this concern and explore a few ways in which analytic theology might be sapiential.